1985
DOI: 10.1111/j.1365-2621.1985.tb00384.x
|View full text |Cite
|
Sign up to set email alerts
|

Modified atmosphere packaging to extend the shelf life of tomatoes

Abstract: An experimental retail packaging system was used to compare the atmospheric composition and relative humidity which developed within packs sealed with a range of plastic films with different permeability properties, and to study the effects of these conditions on the rate of ripening (as indicated by colour change) and sensory quality of tomatoes. In packs sealed with several polyvinylchloride (PVC) films or with K-resin (a butadiene-styrene copolymer), an atmosphere containing 3-9% CO,+3-9% 0, developed withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(28 citation statements)
references
References 9 publications
4
24
0
Order By: Relevance
“…Combrink et al [40] reported that non-perforated polyethylene bags maintained guava fruit quality better than perforated bags. Most workers have used polyethylene and PVC films [58,136] to extend tomato shelf life up to 21 days. Banana is greatly benefited from MAP using LDPE films due to reduced C 2 H 4 sensitivity associated with high CO 2 and low O 2 [7,13,24].…”
Section: Current Application Of Polymeric Films For Map Of Fruits Andmentioning
confidence: 99%
“…Combrink et al [40] reported that non-perforated polyethylene bags maintained guava fruit quality better than perforated bags. Most workers have used polyethylene and PVC films [58,136] to extend tomato shelf life up to 21 days. Banana is greatly benefited from MAP using LDPE films due to reduced C 2 H 4 sensitivity associated with high CO 2 and low O 2 [7,13,24].…”
Section: Current Application Of Polymeric Films For Map Of Fruits Andmentioning
confidence: 99%
“…It shows that (Fig. 4a) the model has achieved an equilibrium concentration of 6 % O 2 (0.06 cm 3 per cm 3 of air) and 4 % CO 2 (cm 3 per cm 3 of air) at 40 h and remains in equilibrium for 100 h. Geeson et al (1985) conducted MA packaging study with tomato of weighing 390 g using 15 μ polyvinylchloride film having void volume of 550 cm 3 at a temperature of 10°C. The equilibrium concentration of O 2 (4 %) and CO 2 (10 %) achieved inside the film package in 200 h using the developed model (Fig.…”
Section: Equilibrium Timementioning
confidence: 99%
“…Among for stored fruits, postharvest losses account to 20-30%. In most of the storability studies for fruits, it is found to be observed that the levels of CO 2 and O 2 inside package altered due to fruit respiration and permeability of the film, resulted in recommendation of modified atmosphere packaging (MAP) for fresh fruit storage (Geeson et al, 1981). When the rate of oxygen and carbon dioxide transmission through the package equal the product"s respiration rate then desirable equilibrium modified atmosphere gets created in the package film at right permeability, edible coatings have long been used for quality retention and shelf life extension of several fresh fruits viz., apple, citrus.…”
Section: Introductionmentioning
confidence: 99%